2022
DOI: 10.1186/s13293-022-00459-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex at the interface: the origin and impact of sex differences in the developing human placenta

Abstract: The fetal placenta is a source of hormones and immune factors that play a vital role in maintaining pregnancy and facilitating fetal growth. Cells in this extraembryonic compartment match the chromosomal sex of the embryo itself. Sex differences have been observed in common gestational pathologies, highlighting the importance of maternal immune tolerance to the fetal compartment. Over the past decade, several studies examining placentas from term pregnancies have revealed widespread sex differences in hormone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 118 publications
1
22
0
Order By: Relevance
“…In humans, pregnancy failure is more likely if the baby is a boy [ 59 , 60 , 61 , 62 ]. Boys grow faster than girls before implantation, and this makes them more vulnerable to compromised nutrition [ 63 , 64 , 65 ]. Probably, in all mammals, life in the maternal uterus is more dangerous for male embryos than for female embryos.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, pregnancy failure is more likely if the baby is a boy [ 59 , 60 , 61 , 62 ]. Boys grow faster than girls before implantation, and this makes them more vulnerable to compromised nutrition [ 63 , 64 , 65 ]. Probably, in all mammals, life in the maternal uterus is more dangerous for male embryos than for female embryos.…”
Section: Discussionmentioning
confidence: 99%
“…PARs are often enriched with genes that code for immune signaling. CD99 is found on a PAR and is significantly higher in the undifferentiated, multipotent progenitor cells of the placenta, the cytotrophoblast (CTB) cells, of males at all points in gestation [68, 72, 73]. An additional study observed clusters of X-linked genes biased toward male overexpression on placental PARs [74].…”
Section: Genetic Influence Of Fetal Sex and Placental Immunitymentioning
confidence: 99%
“…The fetal testes begin synthesizing and secreting testosterone between 8 and 10 weeks of gestation [103]. Fetal circulating testosterone peaks at approximately week 16 and reaches concentrations analogous to circulating androgens in postpubertal males [72]. During this peak period, the testosterone concentrations of amniotic fluid are 2–5-fold higher in male compared with female amniotic fluid [104, 105].…”
Section: Genetic Influence Of Fetal Sex and Placental Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Factors that determine the number of cotyledons are unknown but There is extensive evidence within the literature that demonstrates the impact of sexual dimorphism on fetal growth, development, and organ function (including the placenta) (reviewed in Braun et al, 2022;Kalisch-Smith et al, 2017;Rosenfeld, 2015;Yu et al, 2021). This provided rationale for our presentation of some data parameters stratified as male and female fetuses separately.…”
Section: Fetal Organ Weightsmentioning
confidence: 99%